Hubungan Dukungan Suami Dengan Kecemasan Pada Ibu Hamil Trimester III Di Klinik Fitri Arianti Kecamatan Balai Jaya - Kristina Sembiring; Mustika Tarigan; Maryono Maryono (Jouska: Jurnal Ilmiah Psikologi, 2022)
This study aims to determine the relationship between husband's support and anxiety in third trimester pregnant women at Fitri Arianti Clinic, Balai Jaya District. The sample in this study was 45 pregnant women over the age of 35 in the third trimester. Social support in this study was measured based on aspects namely emotional support, appreciation support, instrumental support, information support. Furthermore, anxiety is measured based on aspects of anxiety, namely physiological aspects, cognitive aspects, behavioral aspects. Based on the results of the analysis using the r Product Moment correlation analysis method, it is known that there is a negative relationship between husband's support. Based on the results of the analysis using the Product Moment r correlation analysis method, it is known that there is a negative relationship between husband's support and anxiety, where rxy = -0.466 with a significant p = 0.000 0.050. This means that the proposed hypothesis is accepted. The determinant coefficient (r2) of the relationship between the independent variable X and the dependent variable Y is r2 = 0.217. This shows that husband's support contributes to anxiety by 21.7%, this shows that there are 78.3% of other factors that influence anxiety such as: Age, education, economy, work, parity, and environment. Based on the results of the calculation of the hypothetical average value and empirically it can be concluded that husband's support is low with a hypothetical mean value of 65 and an empirical mean of 48.69. Furthermore, it can be concluded that anxiety is classified as moderate with a hypothetical value of 12 and an empirical value of 12.09.